2014
DOI: 10.1177/1477153514564174
|View full text |Cite
|
Sign up to set email alerts
|

Modifications to the CIE 115-2010 procedure for selecting lighting classes for roads

Abstract: One of the crucial street lighting design steps considerably influencing electricity consumption is the selection of an appropriate lighting class. Therefore, after a detailed analysis of the current CEN and CIE selection procedures for streets and roads with motor or mixed traffic, several modifications of the CIE 115-2010 procedure are proposed. This way not only is its simplicity maintained but also the agreement between the two procedures is increased by up to 50%. The modifications are related to the weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…A longitudinal uniformity along the center of each lane is recommended for tunnels with a threshold of 0.6. The values of 0.4 and 0.6 are comparable to the average illumination values stipulated by the regulations CIE 115-1995 [20,22].…”
Section: Optical Design Of Led Cbl For Cie Tunnel Road Lightingsupporting
confidence: 70%
See 1 more Smart Citation
“…A longitudinal uniformity along the center of each lane is recommended for tunnels with a threshold of 0.6. The values of 0.4 and 0.6 are comparable to the average illumination values stipulated by the regulations CIE 115-1995 [20,22].…”
Section: Optical Design Of Led Cbl For Cie Tunnel Road Lightingsupporting
confidence: 70%
“…The lens uses the internal reflection and refraction of light to work, which is different from traditional optical LED devices, such as optical reflectors or total internal reflection (TIR) devices [9,18]. Through optical simulation experiments in a trial tunnel in Taiwan, the LED light was demonstrated to be suitable for use as a Counter Beam Light (CBL) and able to meet the CIE 88:2004 regulations for tunnel lighting with appropriate light arrangements [19][20][21].…”
Section: Introductionmentioning
confidence: 99%